Investigation of the properties and production of sawdust ceiling tile using polystyrene as a binder. Issue 6 (2nd November 2017) - Mogaji, Pius Bamidele; Ayodeji, Sesan Peter; Olatise, Ayodeji David; Oladele, Isiaka Oluwole
Abstract : In this research, a production and properties investigation of wood sawdust ceiling tile using polystyrene as a binder was carried out. The content by weight of the wood sawdust was 5, 10, 15, 20, 25 and 30% consisting of three composite samples for each of the six filler content percentages. The samples were prepared in accordance with the American Standard for Testing and Material (ASTM) for wear resistance, flexural and tensile properties as well as water resistance. From the results, it was observed that with the exception of the wear loss, 5% sample gave the best values next to the control sample in almost all the properties. For wear resistance, the value was 0.4568 g and was the sample with the best wear resistance. The result revealed that curing rate is highly influenced by the filler since it decreases as the filler content increases. Higher resistivity was recorded as the filler content increased and this may not be unconnected to the fact that air, being a poor conductor, is more in the composite where we have more filler content.